Recurrent intussusception in children - V. V. Podkamenev; I. A. Pikalo; I. S. Sharapov; E. M. Petrov; M. I. Potemkin; V. Kh. Latypov; N. I. Mikhailov; S. V. Moroz (Вестник хирургии имени И.И. Грекова, 2017)
OBJECTIVE. The study considered the rate and clinical features of recurrent intussusception in children. MATERIAL AND METHODS. Retrospective analysis was made in all patients with intussusception at the period from 2006 to 2016. RESULTS. There were observed 45 cases of intussusception recurrence in 39 (14,5 %) children out of 268. Relapse of intussusception was three times more frequent in boys compared with girls (29 (74,4 %) vs 10 (25,5 %) and it was four times more frequent in children older than one year. The majority of patients (28 (71,8 %) have been admitted to hospital at the first 12 hours since onset of disease. Recurrence of intussusception was more frequent after conservative disinvagination compared with surgery (17,8 % vs 2,5 %; p = 0,026). Pathological formation of the intestine (Meckel’s diverticulum, doubling of the small intestine) were detected in 3 (7,7 %) out of 39 patients with relapse intussusception compared with 3 (1,3 %) out of 229 patients without recurrence (p = 0,05). Conservative treatment was conducted in 23 (59 %) patients and 16 (41,0 %) patients underwent surgery. There weren’t noted severe complications of lethal outcomes. CONCLUSIONS. The authors observed the tendency of frequent recurrence of intussusception in children, especially after conservative treatment.